MFS multidrug transporters in pathogenic fungi: do they have real clinical impact? - Costa, Catarina; Dias, Paulo J.; Sá-Correia, Isabel; Teixeira, Miguel C. (Frontiers in Physiology, 2014)
Infections caused by opportunistic fungal pathogens have reached concerning numbers due to the increase of the immunocrompromised human population and to the development of antifungal resistance. This resistance is often attributed to the action of multidrug efflux pumps, belonging to the ATP-binding cassette (ABC) superfamily and the major facilitator superfamily (MFS). Although many studies have focused on the role of ABC multidrug efflux transporters, little is still known on the part played by the Drug:H+ Antiporter (DHA) family of the MFS in this context. This review summarizes current knowledge on the role in antifungal drug resistance, mode of action and phylogenetic relations of DHA transporters, from the model yeast S. cerevisiae to pathogenic yeasts and filamentous fungi. Through the compilation of the predicted DHA transporters in the medically relevant Candida albicans, C. glabrata, C. parapsilosis, C. lusitaniae, C. tropicalis, C. guilliermondii, Cryptococcus neoformans, and Aspergillus fumigatus species, the fact that only 5% of the DHA transporters from these organisms have been characterized so far is evidenced. The role of these transporters in antifungal drug resistance and in pathogen-host interaction is described and their clinical relevance discussed. Given the knowledge gathered for these few DHA transporters, the need to carry out a systematic characterization of the DHA multidrug efflux pumps in fungal pathogens, with emphasis on their clinical relevance, is highlighted.